Investigation of vehicle body radiation pattern as an antenna transmission system - Naidu, Dineshwaran (2015)
Wireless communication is in high demand in today’s society. The mobility of communication is not limited to the people walking along the streets but also for those who are driving. Therefore, communication inside the vehicles has become more and more important. The problem faced today by the common antenna technology is the strength of its receiving signal. In order to have an effective transmit and receive signals, the car body itself can be turned into an antenna. The main aim in this research is to study and simulate the radio wave distribution along the body of a car. Apart from that, the research also studies the radiation pattern of the waves transmitted or received. Finally, the health issue is also studied and aims to meet the standard SAR requirements. The simulation software used in this study is FEMM (Finite Element Mesh Method) CAD software. FEMM is a finite element method to analyze the electromagnetic radiation generated from the body of a car. The electromagnetic radiation for Mini Cooper and Camaro sport are different in terms of current density, field strength and wave distribution. Apart from that, the mesh size is also different from each other. From the simulation, the electromagnetic field distribution show that the field strength is highly concentrated from within the vehicle due to the antenna source is placed there. Besides that, the H-field strength shows different parts of the car exhibits different types of characteristics when it comes to field intensity distribution. It is seen that Mini Cooper has higher field strength in relation to the material conductivity. Mini Cooper small in size, has lower surface area compared to the Camaro sport car. The small size has a lower resistance but higher conductivity compared to the Camaro sports car. Simulation was also done on different types of frequencies and different types of material properties.